Practice Features Associated With Patient-Reported Accessibility, Continuity, and Coordination of Primary Health Care - Haggerty, Jeannie L. (American Academy of Family Physicians, 2008)
PURPOSE On the eve of major primary health care reforms, we conducted a multilevel survey of primary health care clinics to identify attributes of clinic organization and physician practice that predict accessibility, continuity, and coordination of care as experienced by patients. METHODS Primary health care clinics were selected by stratified random sampling in urban, suburban, rural, and remote locations in Quebec, Canada. Up to 4 family or general physicians were selected in each clinic, and 20 patients seeing each physician used the Primary Care Assessment Tool to report on first-contact accessibility (being able to obtain care promptly for sudden illness), relational continuity (having an ongoing relationship with a physician who knew their particulars), and coordination continuity (having coordination between their physician and specialists). Physicians reported on aspects of their practice, and secretaries and directors reported on organizational features of the clinic. We used hierarchical regression modeling on the subsample of regular patients at the clinic. RESULTS One hundred clinics participated (61% response rate), for a total of 221 physicians and 2,725 regular patients (87% response and completion rate). First-contact accessibility was most problematic. Such accessibility was better in clinics with 10 or fewer physicians, a nurse, telephone access 24 hours a day and 7 days a week, operational agreements to facilitate care with other health care establishments, and evening walk-in services. Operational agreements and evening care also positively affected relational continuity. Physicians who valued continuity and felt attached to the community fostered better relational continuity, whereas an accessibility-oriented style (as indicated by a high proportion of walk-in care and high patient volume) hindered it. Coordination continuity was also associated with more operational agreements and continuous telephone access, and was better when physicians practiced part time in hospitals and performed a larger range of medical procedures in their office. CONCLUSIONS The way a clinic is organized allows physicians to achieve both accessibility and continuity rather than one or the other. Features that achieve both are offering care in the evenings and access to telephone advice, and having operational agreements with other health care establishments.